THE SONG AS A CHILDREN'S WELCOME LANGUAGE - Alessandra dos Santos, Fabiana; Frizzera, Cristiane; Rodrigues de Souza Bassiqueti, Elaine; Aparecida Rocha da Silva, Eliane; Gouvêa de Souza , Elisângela; Aparecida Pereira, Fernanda; Luzes Galvão, Gabrielle; Costa Wathier dos Santos, Juliana; Rodrigues de Oliveira , Maurenice; Aparecida da Silva Moura , Maria; Aparecida Gonçalves Ribeiro, Patrícia; Berbel dos Santos, Roseli; et al. (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this article was to analyze, through a bibliographical research, the contributions that the songs can provide in the development and reception of children who enter kindergarten, such an important phase for motor, cognitive and affective development. The entry of a child into daycare or preschool is a remarkable moment for the child and his family. This is a routine change that requires careful planning by both the family and the pedagogical team of the institution that will host them. The child needs to have his adaptation process to the new routine respected in the most diverse aspects. Therefore, the songs are a playful tool that will help the child to feel welcomed, attracted, respected, and included in this new living space. The use of musicality will also help the educator in the teaching-learning process, as the songs instigate the development of attention, speech, respect among students, body expression, socialization, vocabulary expansion, motor skills and many others, thus promoting, the integral development of children. The songs can be presented in the most diverse ways, such as through electronic sound devices, but on the occasion, we will emphasize the work developed with the use of voice and gestures as an instrument of acceptance, affection and socialization.